THEORETICAL CONCEPT OF A MYOELECTRIC CONTROLLED PROSTHETIC HAND - Yusufov Azizbek; Zafar Juraev (Journal Park Publishing, 2024)
According to user feedback the current models of myoelectric mechanically actuated prosthetic hands are not functional enough for the user, and many users choose to use a passive prosthetic instead even if they own a mechanically actuated one due to the low functionality. The price of these advanced prosthetics is also an issue, especially in third world countries where the need is larger, and the economy is lower.
Keywords: prosthetics, medical chain, bionics, hand geometry, additive manufacturing.